The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1037/xap0000476
|View full text |Cite
|
Sign up to set email alerts
|

Morality in minimally deceptive environments.

Abstract: Psychologists, economists, and philosophers have long argued that in environments where deception is normative, moral behavior is harmed. In this article, we show that individuals making decisions within minimally deceptive environments do not behave more dishonestly than in nondeceptive environments. We demonstrate the latter using an example of experimental deception within established institutions, such as laboratories and institutional review boards. We experimentally manipulated whether participants recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 91 publications
0
0
0
Order By: Relevance
“…When working in collaborative settings, dishonesty can be contagious and spread among group members (Gross et al, 2018) and the impact of collaboration on corrupt behaviors has been related to various factors, including diffusion of responsibility and moral justifications (Conrads et al, 2013;Kocher et al, 2018), perceived similarity (Irlenbusch et al, 2020), commitment (Zickfeld et al, 2022), parochial altruism (Cadsby et al, 2016;Shalvi & De Dreu, 2014), exposure to dishonest descriptive norms (Gross & De Dreu,, 2020;Soraperra et al, 2017) and conformity (Jamaluddin et al, 2020). Conversely, committing to an honesty oath (Beck et al, 2020;Zickfeld et al, 2023), increasing the salience of negative externalities (Castillo et al, 2022), and being monitored (Mitkidis et al, 2023;Schild et al, 2019) have been found to decrease dishonesty.…”
Section: Introductionmentioning
confidence: 99%
“…When working in collaborative settings, dishonesty can be contagious and spread among group members (Gross et al, 2018) and the impact of collaboration on corrupt behaviors has been related to various factors, including diffusion of responsibility and moral justifications (Conrads et al, 2013;Kocher et al, 2018), perceived similarity (Irlenbusch et al, 2020), commitment (Zickfeld et al, 2022), parochial altruism (Cadsby et al, 2016;Shalvi & De Dreu, 2014), exposure to dishonest descriptive norms (Gross & De Dreu,, 2020;Soraperra et al, 2017) and conformity (Jamaluddin et al, 2020). Conversely, committing to an honesty oath (Beck et al, 2020;Zickfeld et al, 2023), increasing the salience of negative externalities (Castillo et al, 2022), and being monitored (Mitkidis et al, 2023;Schild et al, 2019) have been found to decrease dishonesty.…”
Section: Introductionmentioning
confidence: 99%